2017
DOI: 10.1002/hbm.23564
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated intrinsic connectivity within cognitive control network among individuals with remitted depression: Temporal stability and association with negative cognitive styles

Abstract: Many individuals with major depressive disorder (MDD) experience cognitive dysfunction including impaired cognitive control and negative cognitive styles. Functional connectivity MRI studies of individuals with current MDD have documented altered resting-state connectivity within the default-mode network and across networks. However, no studies to date have evaluated the extent to which impaired connectivity within the cognitive control network (CCN) may be present in remitted MDD (rMDD), nor have studies exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 82 publications
8
61
0
Order By: Relevance
“…We included bilateral dorsolateral prefrontal cortex nodes within the middle frontal gyrus (+/−45 29 32), inferior parietal lobule (+/−52 −50 49), and dorsal anterior cingulate (+/−5 22, 47) to use as seeds in the connectivity analysis (Yeo et al, 2011). For each of these three bilateral seeds, we ran cross-correlation time series analyses as described above (and similar to Stange et al, 2017). Similar procedures were used for three bilateral seeds for the SEN [amygdala (+/−23 −5 −19; Jacobs et al, 2014), ventral striatum inferior (+/−9 9 −8; diMartino et al, 2008), anterior insula (+/−33 12 −6; Deen et al, 2011)] and for the DMN [posterior cingulate (+/−5 −49 25), dorsal medial cingulate (+/−7 46 −2), temporoparietal junction (+/−49 −63 45)] (Yeo et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included bilateral dorsolateral prefrontal cortex nodes within the middle frontal gyrus (+/−45 29 32), inferior parietal lobule (+/−52 −50 49), and dorsal anterior cingulate (+/−5 22, 47) to use as seeds in the connectivity analysis (Yeo et al, 2011). For each of these three bilateral seeds, we ran cross-correlation time series analyses as described above (and similar to Stange et al, 2017). Similar procedures were used for three bilateral seeds for the SEN [amygdala (+/−23 −5 −19; Jacobs et al, 2014), ventral striatum inferior (+/−9 9 −8; diMartino et al, 2008), anterior insula (+/−33 12 −6; Deen et al, 2011)] and for the DMN [posterior cingulate (+/−5 −49 25), dorsal medial cingulate (+/−7 46 −2), temporoparietal junction (+/−49 −63 45)] (Yeo et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Subsets of these samples have been reported in prior work, including from MH091811 awarded to Langenecker (Bessette et al, 2018;Bhaumik et al, 2017;DelDonno et al, 2017;Jacobs et al, 2014Jacobs et al, , 2016Jenkins et al, 2017;Rao et al, 2016;Stange et al, 2017), MH086517 awarded to Monk and Phan (Hamm et al, 2014;Wu et al, 2016), UIC CCTS UL1TR000050, Mind and Life Foundation, and Klingenstein Third Generation Foundation Fellowship awarded to Jacobs Peters et al, 2016). Data is also present from MH101487 (awarded to Langenecker).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasic et al observed increased functional connectivity in the left DLPFC during a working memory task in MDD. However, Stange et al reported attenuated CCN connectivity which was stable over time in remitted MDD. Aizenstein et al reported reduced DLPFC‐dACC functional connectivity on an executive‐control task in patients with late‐life depression (LLD).…”
Section: A Network Model Of Major Depressionmentioning
confidence: 98%
“…In contrast, connectivity during a facial emotion perception task, even when task events are removed, is specific to performance of an emotion perception task. Finally, although we have previously demonstrated that within-network SEN connectivity did not differ by group (Stange et al, 2017, Supplement) and there were no significant group differences in performance in the present study, to ensure that there were no differential associations between performance and connectivity by group, we conducted moderation analyses on the extracted beta values from the significant clusters in Tables 1 and 2. These results are reported in the Supplement.…”
Section: Discussionmentioning
confidence: 94%